ANALISIS KONTRIBUSI PENDAPATAN WANITA TANI DALAM KEGIATAN PASCA PANEN BAWANG MERAH DI KABUPATEN BREBES - Indah Nurhidayati (Universitas Teuku Umar, 2018)
Basically women have job opportunities that can generate income for their needs as an effort to reduce poverty. Similarly, women farmers in Brebes District are involved inonion post-harvest activities. This study aims to analyze the income of women farmers inonion post-harvest activities and its contribution to total household income. The study was conducted from February to March 2018. The analysis method used was income analysis and income contribution. The results showed that the average income of 45 female farmers respondents reached Rp70,333.00 per day, with income contribution reaching 63,058 percent to total household income. The condition shows that the involvement of women in onion post-harvest activities in Brebes District is the main role.